The Implementation of Creative Problem Solving Model in Teaching of Biodeviersity at Senior High School - Fatmawati, Baiq; Roshayanti, Fenny; Ha, Minsu (Universitas Muhammadiyah Mataram, 2023)
Abstract: Making students to be creative thinking need exercises in the form of tasks. Creative problem solving is the constructivist learning model to create creative, imaginative, and innovative solutions in the aim of training and teaching individuals to think differently in solving problems.The research focus was to find out students' learning outcome and creative thinking skills using creative problem solving-based learning. The participants were tenth grade of senior high school in the school year 2019/2020 which were divided into science class as the control class (N=33), and X IPA 2 class as the experimental class (N=33). The research instrument used was a description test on biodiversity content with creative problem solving indicators, namely Clarify, Ideate, Develop, and Implement. Quantitative data analysis used was MANOVA test at a significant level of 5%. The results of this study were the average values for each indicator of creative thinking and learning outcomes in the experimental and control classes showing that the control class was lower than the experimental class. It means that learning outcomes and creative thinking skills through creative problem solving had an impact than the classes using creative problem solving. Therefore, there was a significant influence and a relationship among the creative problem-solving model, creative thinking skills, and learning outcomes which was indicated by the value of. 0.000<0.05.